2015
DOI: 10.1002/2015wr017018
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and landscape controls on water transit times and silicate mineral weathering in the critical zone

Abstract: The critical zone (CZ) can be conceptualized as an open system reactor that is continually transforming energy and water fluxes into an internal structural organization and dissipative products. In this study, we test a controlling factor on water transit times (WTT) and mineral weathering called Effective Energy and Mass Transfer (EEMT). We hypothesize that EEMT, quantified based on local climatic variables, can effectively predict WTT within-and mineral weathering products from-the CZ. This study tests wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 76 publications
7
56
0
Order By: Relevance
“…Our soil water samples at the plot scale support the interpretation of catchment scale isotope studies in northern latitudes and/or regions with snow cover (Jasechko, Wassenaar, & Mayer, ; Scheliga, Tetzlaff, Nuetzmann, & Soulsby, ; Sprenger, Tetzlaff, Tunaley, Dick, & Soulsby, ; Zapata‐Rios et al, ) that the most intense recharge of groundwater occurs from waters depleted in heavy isotopes such as snowmelt (Dry Creek, Dorset, Krycklan, Wolf Creek) and winter rainfall (Bruntland Burn). At Dry Creek, the soil pores get filled during the snowmelt in early spring, and this melt water stays in the soil over the summer, because little precipitation occurs then.…”
Section: Discussionsupporting
confidence: 79%
“…Our soil water samples at the plot scale support the interpretation of catchment scale isotope studies in northern latitudes and/or regions with snow cover (Jasechko, Wassenaar, & Mayer, ; Scheliga, Tetzlaff, Nuetzmann, & Soulsby, ; Sprenger, Tetzlaff, Tunaley, Dick, & Soulsby, ; Zapata‐Rios et al, ) that the most intense recharge of groundwater occurs from waters depleted in heavy isotopes such as snowmelt (Dry Creek, Dorset, Krycklan, Wolf Creek) and winter rainfall (Bruntland Burn). At Dry Creek, the soil pores get filled during the snowmelt in early spring, and this melt water stays in the soil over the summer, because little precipitation occurs then.…”
Section: Discussionsupporting
confidence: 79%
“…Based on the thermodynamic theory, Rasmussen et al [] developed an integrated framework to quantify effective energy and mass fluxes into the critical zone. Previous research [ Chorover et al , ; Rasmussen et al , ; Zapata‐Rios et al , ] has validated that the quantification of EEMT can predict the structure and function of the CZ. For example, Zapata‐Rios et al [] found good correlations between EEMT, mineral weathering, and water transit times.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [ Chorover et al , ; Rasmussen et al , ; Zapata‐Rios et al , ] has validated that the quantification of EEMT can predict the structure and function of the CZ. For example, Zapata‐Rios et al [] found good correlations between EEMT, mineral weathering, and water transit times. This study proves the value of EEMT in reflecting CZ thickness (see Table ): EEMT explains 19% of the variance in GWT, 6.3% in WTD, 5.1% in CZT, and 2.7% in the underground part (CZTsub); E BIO also plays important roles, e.g., it explains 8.8% of the variance in GWT and 8.4% in WTD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation ranges from about 1700 m to 3370 m (Redondo Peak), and the climate is generally semi-arid to continental [61]. Mean annual precipitation over the past 31 years (1981-2012), based on the nearest Snow Telemetry (SNOTEL) station (Quemazon station; located 13 km northeast of Redondo Peak), is 711 mm equally contributed by summer monsoon rainfall and wintertime snowfall [62]. …”
Section: Study Areamentioning
confidence: 99%